PENENTUAN KESERAGAMAN RESPON DAN FAKTOR KOREKSI TLD – 100 (LiF:Mg,Ti) TERHADAP RADIASI SINAR-X - Syaphira Faza Nurulita; Wahyu Setia Budi; Eko Hidayanto; Nunung Nuraeni (BERKALA FISIKA, 2023)
One  of  the  body  tissues  of  radiation  workers  that  is  very  sensitive  to  exposure  to  X-ray radiation  is  the  eye  lens.  Damage  experienced  by  the  lens  of  the  eye  exposed  to  X-ray radiation  can  develop  until  blindness  occurs  due  to  cataracts.  The  use  of  a Thermoluminescence  Dosemeter  (TLD)  can  control  the  external  radiation  dose  received  by the  eyepiece  of  radiation  workers.  In  this  study  there  are  several  objectives,  namely  to determine  the  uniformity  of  the  response  to  TLD-100  (LiF:Mg,Ti)  to  determine  the characteristics of TLD-100 (Lif:Mg,Ti) which is used to measure the radiation dose of the eye lens  and  determine  the  TLD-100  correction  factor  on  X-ray  radiation  to  obtain  an  accurate dose  of  TLD-100  readings  in  the  eyepiece.  The  determination  of  the  uniformity  of  reading response and correction factor of TLD-100 (LiF:Mg,Ti) was carried out on the surface of the water  phantom  using  conventional  X-ray  radiation  sources  with  variations  in  voltage (60;70;80) kV at a distance of 100 cm and a wide field. used is 26 x 26 cm. From the results obtained for determining the uniformity of the response of TLD-100 at voltage (60;70;80) kV using  Statistical  Process  Control  (SPC)  analysis  it  can  be  concluded  that  TLD-100  has  a uniform response because it is between the Lower Warning Limit (LWL) and Upper Warning Limit  (UWL).  However,  according  to  ISO  21909  at  a  voltage  of  60  kV  it  is  necessary  to  re- illuminate  because  the  response  variation  value  obtained  is  40.95%  exceeding  the  specified response variation value limit which is not more than 20% while at a voltage of 70 kV with a response  value  of  20.05%  and  80  kV  with  a  response  variation  value  of  13.93%  did  not exceed  the  predetermined  limits  while  the  results  of  determining  the  TLD-100  correction factor (LiF:Mg,Ti) for each voltage decreased in the range of 0.753 to 0.576. The correction factor at a voltage of 60 kV to 80 kV does not reach the ideal correction factor because the voltage  used  for  calibration  uses  low  energy  while  the  calibration  used  is  for  calibration  at high voltages.